WEB-BASED EVENT SEMINAR REGISTRATION INFORMATION SYSTEM APPLICATION - Rizky Febryan; Rogape Iansen Euclerr; Yulia Wardaningsih; Fajar Masya (Kresnamedia Publisher, 2020)
Information on the list of seminar events and seminar registration which is still done manually results in limited information access being given to the seminar participants, besides the data processing process carried out by the committee becomes less effective and efficient. To solve these problems, an online computerized information system is needed that can provide information related to seminar participant registration, data management, and seminar events. With the implementation of this system, it is expected to facilitate access to information about the seminar event schedule and reduce the risk of recording errors in seminar participant registration. This system is also expected to further accelerate the process of making reports which in turn can help the performance of the seminar committee. The research method used is a survey method involving certain people, especially students. Whereas the system development method (SDLC) is carried out using the waterfall method.